Clinical Significance of CBCT Findings in the Treatment of Maxillary Cysts Expanded Into the Nasal and Sinus Cavities - Yalçın, Mustafa; Demirkol, Mehmet (European Journal of Therapeutics, 2023)
Objective: We aimed to retrospectively assess the importance of the radiological findings from the cone-beam computed tomography (CBCT) data on the treatment of maxillary cysts extending into the nasal and maxillary sinus cavities. Methods: Thirty-three consecutive patients with maxillary intraosseous odontogenic cysts that extended into the nasal and maxillary cavities were included in the present study. The CBCT signs of the lesions were classified into three subgroups for lesions extending into the maxillary sinus and divided into four subgroups for lesions extending into the nasal cavities. Age, gender, cyst type, location, presence of cortical bone expansion/resorption, root displacement, lacunarity (unilacunar and multilacunar), and lesion dimensions were also evaluated. All the patients were treated with only enucleation, only decompression, or decompression after enucleation. Here, p<0.05 was considered to be statistically significant. Results: Patients (13/39.4% females and 20/60.6% males) were in the age range from 8 to 65 years (mean age: 30.42±12.74 years). Here, 23 cases, (69.7%) exhibited both buccal and palatine bone resorption as compared to only cortical resorption in the coronal CBCT slices. The cysts’ dimensions were calculated from the axial, coronal, and sagittal slices as 24.58±8.56, 24.94±9.74, and 26.45±7.88 mm, respectively. There were no statistically significant differences between both the subgroups of the CBCT findings of lesions extending in the nasal area or maxillary sinus as well as the three treatment modalities (p>0.05). Conclusion: The resorption of the lateral nasal wall and cortical floor, particularly in the nasal region, and the findings of narrowing of the airway may affect treatment planning, even if the obtained results were not statistically significant